Critical indigenous studies : engagements in first world locations - Moreton-Robinson, Aileen (Critical issues in indigenous studies., 2016)
This is an edited volume with contributions by leading scholars on the central epistemological, theoretical, political, and pedagogical questions and debates that constitute the discipline of Indigenous Studies. The volume emerges from a 2012 symposium hosted by the Indigenous Studies Research Network at Queensland University of Technology. The volume is organized into three sections: the first section includes essays that interrogate the embeddedness of Indigenous studies within academic institutions; the essays in the second section explore the epistemology of the discipline; and the third section's essays are devoted to understanding the locales of critical inquiry and practice. Moreton- Robinson's introductory essay provides a brief history of the discipline.